A novel poly(ethyleneoxide)-based magnetic nanocomposite catalyst for highly efficient multicomponent synthesis of pyran derivatives. Issue 4 (2nd October 2018) - Maleki, Ali; Azizi, Mojtaba; Emdadi, Zeynab
ABSTRACT: In the present work, a new magnetically recyclable nanocomposite catalyst was designed, prepared, and characterized by Fourier transform infrared (FT-IR) spectroscopy, field-emission scanning electron microscopy (FE-SEM) images, X-ray diffraction (XRD) pattern, energy-dispersive X-ray (EDX), vibrating sample magnetometer (VSM), and transmission electron microscopy (TEM) analyses. Then, the catalytic activity of the prepared Fe3 O4 /PEO/SO3 H nanocatalyst was examined on multicomponent synthesis of 2-amino-3-cyano-4H-pyranes. Short reaction time, room temperature, good-to-excellent yields, easy catalyst separation and catalyst reusability, environmentally benign and efficient conditions are some advantages of this green protocol. GRAPHICAL ABSTRACT: